Graptoppia (Graptoppia) paraanalis Subias and Rodriguez 1985 - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Graptoppia (Graptoppia) paraanalis Subias and Rodriguez, 1985 * Material – New record for Turkey. One specimen in Çiftlik Village, Tekçam Area, Taşköprü forest, Kastamonu, N 41° 27′ 39.53′′, E 34° 19′ 42.99′′, alt. = 898 m, 5 June2018; one specimen in Yeşiltepe Area, Akçaabat, Trabzon, 27 May 2018, N 40° 58′ 24.75′′, E 39° 30′ 25.55′′, alt. = 348 m; seven specimens in Alasökü Village,Taşköprü forest, Kastamonu, 16 June 2018, N 41° 20′ 09.64′′, E 34° 25′ 58.98′′, alt = 1327 m; three specimens in Çamkonak Forests, Daday, Kastamonu, 09 October 2018, N 41° 23′ 54.24′′, E 33° 13′ 13.73′′, alt. = 1147 m. Tree bark and debris of P. abies and P. nigra. Global distribution – Palaearctic. Ecology – Litter and soil. Remarks – Turkish individuals are larger (285 × 155 µm) than reported by Subías and Rodriguez (1985) for Spanish and Italian specimens (232–245 µm). All other characters match the original description (Subías and Rodriguez 1985).

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on pages 261-262, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Graptoppia; Arachnida; Graptoppia paraanalis; Animalia; Biodiversity; Sarcoptiformes; Oppiidae; Taxonomy; 15. Life on land